Pembasmian Kemiskinan Bandar ke arah Bandar Inklusif dan Sejahtera: Cabaran Kuala Lumpur - Wan Abd Aziz, Wan Nor Azriyati; Ahmad, Faizah; Hanif, Noor Rosly (Journal of Surveying, Construction and Property, 2011)
Urban poverty is a dynamic condition of vulnerability due to urban management. This paper seeks to examine the extent to which the housing programs targeted at addressing urban poverty in the city of Kuala Lumpur, Malaysia achieved their target. Based on mixed-method approaach, the study aims to assess the scope of poverty, and to identify its characteristics and determinants. It establishes that City Hall of Kuala Lumpur has long provided affordable housing and employment opportunity to low-income households but the policy responses and program options designed to reduce urban poverty mismatched the key policy objective to reduce the poor households‟ vulnerability. The local authority needs to revisit the current programs for poverty eradication of the urban poor in its effort towards an inclusive and livable city. Keywords: urban poverty, affordable housing, housing policy, poverty reduction, livable city. Abstrak